2022
DOI: 10.21608/aimj.2023.144105.1986
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic function of office hysteroscopy and three-dimensional (3D) endometrial volume measurement in the evaluation of women with perimenopausal bleeding

Abstract: Background: In the peri-and postmenopausal years, abnormal uterine bleeding (AUB) is the most prevalent reason for gynecological appointments. Aim of the work:To see how office hysteroscopy and three-dimensional (3D) ultrasonographic measurements of endometrial volume affected endometrial volume and if those methods could predict malignant conditions and hyperplasia of the endometrium and if they could exclude serious intrauterine pathology in perimenopausal women with irregular uterine bleeding to minimize fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
2
0
0
Order By: Relevance
“…Normal and atrophic endometrium was observed in 37.3% of cases, while endometrial hyperplasia was observed in 54.2% and endometrial polyps in 6.8%. These results are in line with previous studies that have reported a higher incidence of benign results in women with postmenopausal bleeding (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
“…Normal and atrophic endometrium was observed in 37.3% of cases, while endometrial hyperplasia was observed in 54.2% and endometrial polyps in 6.8%. These results are in line with previous studies that have reported a higher incidence of benign results in women with postmenopausal bleeding (12)(13)(14).…”
Section: Discussionsupporting
confidence: 93%
“…Also, our findings in line with Nafad et al (14) who demonstrated that menorrhagia accounted for 31 percent of instances, whereas menometrorrhagia (28 percent), metrorrhagia (21 percent), and polymenorrhoea (20 percent) were the most prevalent bleeding patterns.…”
Section: Discussionsupporting
confidence: 92%